2015
DOI: 10.4049/jimmunol.1400402
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of Hypoallergenic Hybrid Proteins for Vaccination against Grass Pollen Allergy

Abstract: More than 10% of the population in Europe and North America suffer from IgE-associated allergy to grass pollen. In this article, we describe the development of a vaccine for grass pollen allergen-specific immunotherapy based on two recombinant hypoallergenic mosaic molecules, designated P and Q, which were constructed out of elements derived from the four major timothy grass pollen allergens: Phl p 1, Phl p 2, Phl p 5, and Phl p 6. Seventeen recombinant mosaic molecules were expressed and purified in Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…However, in spite of beneficial clinical efficacy, recombinant allergen preparations revealed poor immunogenicity, and therefore they do not induce significantly better therapeutic effects than natural extracts [8,9]. Moreover, there is a need for employment of novel immunomodulators capable to enhance the innate immune response in order to economically justify the production of recombinant allergy vaccines [10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, in spite of beneficial clinical efficacy, recombinant allergen preparations revealed poor immunogenicity, and therefore they do not induce significantly better therapeutic effects than natural extracts [8,9]. Moreover, there is a need for employment of novel immunomodulators capable to enhance the innate immune response in order to economically justify the production of recombinant allergy vaccines [10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…7). In all of the four sera, it was observed that TYKW-mut did not reach an IC 50 value at a concentration as high as 10 4 ng in 100 l of each serum (i.e. 100 g/ml).…”
Section: Reduction In Ige Binding To Rhi Omentioning
confidence: 99%
“…H&E and PAS staining of lung histology were done to quantify the eosinophilic infiltrates and mucous gland hyperplasia, respectively, as described (49). For raising antisera, three BALB/c mice (10 g of antigens/mouse) and one New Zealand White rabbit (200 g of antigens/rabbit) were immunized with either rRhi o 1 or TYKW-mut adsorbed to Freund's adjuvants following protocols described previously (50). About 3-4 mg of IgG were purified from rabbit sera (preimmune and immune) using a Pierce TM Protein A IgG purification kit.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, a clinical improvement was observed by treatment with the recombinant birch pollen allergen Bet v 1 . Although clinical trials with recombinant allergen preparations revealed good clinical efficacy, their poor immunogenicity represents a problem, as it does not induce significantly better therapeutic effects than natural extracts . Therefore, the application of novel immunomodulators capable of activating the innate immune response might economically justify the production of recombinant allergy vaccines …”
Section: Introductionmentioning
confidence: 99%